Economic, Social and Environmental Impacts of Sultan Thaha Syaifuddin Forest Park Due to Oil Palm Plantation Expansion in Bungku Village, Batanghari Regency, Jambi Province - Ahmad Mubarok; Annisa Putri; Eka Intan Kumala Putri; Meti Ekayani (Jurnal Ilmu Lingkungan, 2026)
Oil palm (Elaeis guineensis) is a strategic plantation commodity that contributes significantly to Indonesia’s economy; however, the expansion of oil palm plantations may generate social and environmental impacts. This study aims to analyze the economic, social, and environmental impacts of oil palm plantation expansion on farming communities surrounding the Sultan Thaha Syaifuddin Forest Park (Tahura STS), Batanghari Regency, Jambi Province. The study employed a random sampling method with respondents selected purposively. Income analysis was used to estimate economic benefits, while descriptive analysis was applied to identify social and environmental impacts. The results indicate that oil palm plantation expansion increased farmers’ average income by 47% in the on-farm sector and provided additional income in the off-farm (21%) and non-farm (32%) sectors, resulting in an average total income increase of 23%. However, plantation expansion also triggered social conflicts between local communities and migrants and generated environmental impacts, including reduced groundwater availability, increased forest fire risk, and declining tree biodiversity.